The chemistry of polymers - Nicholson, John W. (Royal Society of Chemistry, 2006)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. The Chemistry of Polymers, Third edition, is a well established and highly readable introductory text book on polymer science, ideal for chemists requiring a broad introduction to the subject. Like its predecessors it has been written primarily from an applications point of view, emphasising practical applications and providing a comprehensive introduction on all aspects of polymer science including polymer synthesis, characterisation, reaction kinetics and materials science. Specialised topics such as polymer degradation, polymers and pollution and a variety of technological developments are also discussed in an informative and up-to-date manner. This third edition of the book has been extensively revised to include the latest developments in polymer science. Highlights and updates include a new chapter on dendrimers - a field of chemistry that has grown enormously in the last ten years. Coverage of 'Special topics in polymer chemistry' and 'Polymers in the environment' have both been updated to reflect recent developments in the field, including polymer recycling. This text is essential reading for university students, teachers and scientists who wish to acquire an up-to-the-minute overview of polymer science and its many specialised topics in an informative and easy to read style.
Previous edition: 1997.
Keywords: Polymers.; Polymerization.; elektronické knihy; electronic books